LABORATORIUM MATEMATIKA DAPAT MENINGKATKAN PEMAHAMAN KONSEP TEOREMA PYTHAGORAS PADA SISWA KELAS VIIIA MTs MU’ALLIMIN MUHAMMADIYAH ALABIO - Nahrawi Nahrawi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
The classroom action research implementing mathematics laboratory as learning resources on Pythagoras Theorema concept was conducted. The objectives of this study was to describe student’s activities and mastery learning outcomes. in the 8 th grade class of MTsN 1 Muallimin Muhammadiyah Alabio with the mathematics laboratory for measurement learning. Subjects were 17 students involved on this study. The Class action research conducts in 2 cycles. Each cycle consists of planning, acting, observing, evaluating and reflecting.. The data collected in the form of student’s activities, achievments and mastery learning outcomes  through tests and observation. Results indicated that mastery learning outcomes of students has increased from cycle I to II, which is 70.57% and 94.12%. The quality of student’s activity also increased from good to the best category.  Key words : Mathematics laboratory, Pythagoras Theorema, mastery learning outcomes, student’s activities